PREVENTION OF CORONA VIRUS INFECTION (COVID19) IN HEALTH WORKERS AND MATERNAL HEALTH SERVICE SUPPORT PERSONAL IN COMMUNITY HEALTH CENTER AREA KOTA TIMUR OF GORONTALO CITY - Yusni Podungge; Siti Choirul Dwi Astuti; Tumartony T.Hiola; Ika Suherlin (Universitas Respati Yogyakarta, 2021)
Prevention Of Corona Virus Infection (COVID-19) In Health Workers and Maternal Health Service Support Personal In Community Health Center Area Kota Timur Of Gorontalo CityBackground: the East City Health Center was chosen because it has patients exposed to COVID 19 with a target of 611 pregnant women. Pregnant women have a high risk if exposed to COVID-19. So it is necessary to prevent COVID-19 infection in the form of providing personal protective equipment (PPE), counseling on COVID-19 infection prevention guidelines, mentoring, monitoring, and evaluation through Whatsapp groups. In this activity, a questionnaire was also given that was filled out via a google form. The questionnaire was used to measure age, education, gravida, and knowledge of preventing COVID-19 infection in maternal services. Objectives: the purpose of this activity is to provide PPE that is used for maternal health service operations carried out at the East City Health Center as well as masks and hand sanitizers for patients, guidebooks that already have ISBNs and are registered with intellectual property rights, increase knowledge of preventing COVID-19 infection and not find patients exposed to COVID-19. Methods: this type of research includes quantitative research with the method of observational analysis. In this study, respondents were 18 health workers at the Puskesmas and 100 pregnant women who did antenatal checks from April to November 2020. The data analysis used the Fisher exact test. Results: the results of the analysis showed that 83% of health workers had good knowledge, 58% of pregnant women had good knowledge, 81% of respondents were in the healthy reproductive category, 64% had a college education and 46% of pregnant women were in the primigravida category. From the results of the questionnaire, data analysis was carried out with the results of the Fisher exact test, sig = 0.0012 (Sig <0.05) for knowledge, age, education, and sig = 0.628 (Sig > 0.05) for gravida. Conclusion: prevention of COVID-19 virus infection in maternal services has a relationship with the knowledge of health workers, knowledge of pregnant women, reproductive age of pregnant women, the last education of pregnant women and has nothing to do with gravida.